ENVIRONMENTAL – HYDROGEOLOGICAL INVESTIGATIONS ON THE CLAY DEPOSITS IN THE BROAD AREA OF MESOLOGGI – AITOLIKO LAGOONS - Zagana, E.; Lemesios, I.; Charalambopoulos, S.; Katsanou, K.; Stamatis, G.; Lambrakis, N. (Bulletin of the Geological Society of Greece, 2010)
A hydrogeological study took place in the broader area of Mesologgi – Aitoliko lagoons (West Greece) aiming at the investigation of a) the hydrogeological conditions of the area as well as the surface and groundwater influences on the quality of the clay deposits found in the lagoons and b) the properties of the clay in order to be identified as “therapeutic peloids”. Due to their location, the clay deposits could be influenced and possibly polluted from the surface waters. The aquifer of the unconsolidated formations presents low hydraulic conductivity, while the carbonate aquifer is bounded from the foregoing aquifer and therefore the possibility of clay pollution from the groundwater is very limited. pH of the sediments showing neutral and alkaline values, limits the mobility of some pollutants. Seawater affects some of the clay samples, which present high electrical conductivity. Iron and manganese show also high concentrations, while some of trace elements such as Cd, Hg, Hf, Be, Ag present concentrations under the detection limit. Most of the organic material of the clay consists of humus and therefore they could be suitable for fangotherapy.